Investigate Students’ Perception of Learning Environment Through Socioscientific Inquiry-Based Learning (SSIBL) Viewed from School Origin and University Entrance - Tri Padila Rahmasari; Jimmi Copriady; Radjawaly Usman Rery (AL-ISHLAH: Jurnal Pendidikan, 2023)
The quality of a good learning environment will affect the effectiveness of a learning model in achieving several competencies in science learning. This research aimed to investigate students' perceptions of the learning environment towards the implementation of Socioscientific Inquiry Based Learning (SSIBL) model on chemical kinetics material. The sample in this study involved 36 students who took Basic Chemistry I course. The data were collected by administering the WIHIC Questionnaire (What is Happening in This Classroom?) consisting of 50 questions. In the WIHIC questionnaire that has been distributed there are 7 indicators that will determine the quality of the learning environment created including student closeness, lecturer support, involvement, investigation, task orientation, collaboration, and student equality. The  questionnaire data were analyzed using the SPPS program by inferring the mean and standard deviation that had been distributed to 69 respondents. The results of the analysis showed that overall the indicators measured were in the very good category. The results of the One way ANOVA analysis state that there is no significant differences in the learning environment of students based on their school origin or university entrance route. This shows that the SSIBL model is a learning alternative that can created a good quality learning environment for all levels of student ability based on school origin and university line.